Challenges in Community Participation for Village Governance Planning - Briansyah , Muchammad Puja; B, Ahmad Riyadh Umar (Indonesian Journal of Cultural and Community Development, 2024)
General Background: Community involvement is vital in Indonesia's local governance, particularly through village deliberations. Specific Background: Kemiri Village in Sidoarjo faces challenges in effectively utilizing Musyawarah Desa due to limited participation and knowledge among decision-makers. Knowledge Gap: While previous studies indicate low engagement, few address specific barriers in Kemiri's context. Aims: This research explores the role of Village Deliberation in formulating the Kemiri Village Government Work Plan, focusing on community needs. Results: Findings reveal that while Musyawarah Desa facilitates discussions, issues like low attendance and inadequate decision-maker knowledge impede effective planning. Novelty: The study applies Mintzberg’s theoretical framework to analyze village deliberation dynamics, offering new insights into rural governance. Implications: Enhancing community participation and decision-maker competency is crucial for effective local governance and sustainable development in Kemiri Village. Highlights: Importance of Community Engagement: Active participation in Musyawarah Desa is crucial for effective local governance and addressing community needs. Barriers to Participation: Limited knowledge among decision-makers and low community attendance hinder optimal planning outcomes in Kemiri Village. Theoretical Framework Application: The study employs Mintzberg’s framework to analyze the dynamics of village deliberation, providing new insights into rural governance. Keywords: Village Deliberation, Community Participation, Local Governance, Work Plan